Time to Endoscopy and Outcomes in Upper Gastrointestinal Bleeding - Nitin Sarin; Neerav Monga; Paul C Adams (Canadian Journal of Gastroenterology)
BACKGROUND: Upper gastrointestinal bleeding (UGIB) is a common problem associated with significant morbidity and mortality. Previous studies show that immediate endoscopies do not affect outcomes in patients; however, endoscopic interventions have evolved. The present retrospective review of endoscopies performed at a large teaching hospital assessed the timing of endoscopy with respect to the morbidity and mortality of UGIB.